Study of Purified Cellulosic Pulp and Lignin Produced by Wheat Straw Biorefinery - Kalvin Durand; Rodrigue Daassi; Denis Rodrigue; Tatjana Stevanovic (Macromol)
With the world population rising, wheat straw production is expected to reach 687–740 million tons per year by 2050. Its frequent application as a fuel source leads to air, water, and soil pollution. Limited literature exists on methods for separating components of residual wheat straw. Optimal conditions for organosolv pulping of hydrolyzed wheat straw include 3% FeCl3·6H2O as a catalyst, a biomass-to-solvent ratio of 1:15 (m/v), and 50% ethanol:water as cooking liquor at 200 °C for 30 min. Desilication conditions involve extraction with 7.5% Na2CO3 at a biomass-to-solvent ratio of 1:20 (m/v) treated at 115 °C for 60 min. Lignin from hydrolyzed wheat straw showed similar properties to organosolv lignin from untreated straw, with minimal lignin alteration during hydrolysis. Hydrolysis significantly degraded cellulose. A 41% lignin recovery rate with 95% purity was achieved from pre-extracted hydrolyzed straw. Recovered cellulose after silica removal had 2% ash and 87% purity. The innovation of this process lies in the development of a comprehensive, sustainable, efficient, and economically viable biorefinery process that efficiently separates key components of wheat straw, i.e., xylose, lignin, cellulose, and silica, while addressing environmental pollution associated with its traditional use as fuel.